(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article includes the process of machining various deep hole surfaces using a steady rest. This process improves surface cleanliness and provides high quality. For the creation of small-diameter deep holes, it is advisable to use methods that ensure high precision and surface cleanliness, enhance the machinability of parts, and maintain a surface hardness of no less than HRC≤445. These include burnishing and broaching methods.